Pengembangan Media Pembelajaran Google Site Dalam Meningkatkan Kreativitas Peserta Didik Pada Pembelajaran Pendidikan Pancasila - Apriani Kusuma Ayu; Ria Yuni Lestari; Reza Mauldy Raharja (Journal of Civic Education, 2022)
In today's digital age, the use of innovative learning media is on the rise, and one such media that has proven to be effective is Google site. This platform offers a plethora of interactive features such as videos and quizzes that can be customized to meet specific learning objectives. This study focuses on the use of Google site as a teaching aid for Pancasila Education in class VII at SMP 4 Serang, Banten, where students have expressed a lack of interest in the subject. Employing a Research and Development (R&D) methodology, this study aims to develop an effective teaching tool that fosters creativity in students. Results indicate a significant improvement in students' creativity levels, as evidenced by pretest and posttest scores. Furthermore, the response from 36 students who used Google site in class VII SMPN 4 Kota Serang was overwhelmingly positive, scoring 120.7, with a percentage of 80.5%, indicating a "High" rating.